Decomposição e liberação de nitrogênio da palha cana-de-açucar em função do ambiente e quantidade de palha - Dietrich, Guilherme (2014)
The sugarcane residues came out as an important source of biomass for the production of cellulosic ethanol in Brazil. However, there is a lack of studies on the impact that how partial removal of these residues affect the decomposition of the remaining crop residue on the soil surface. In this context, the aim of this study was to evaluate the decomposition and release of nitrogen (N) from sugarcane residues under field conditions. Three different rates of residues were evaluated at five different location of the Rio Grande do Sul state, Brazil. The study was conducted from September 2012 to August 2013, in the municipalities of Port Xavier, São Luiz Gonzaga, Jacuí Heels, Santa Maria and Pelotas. The experimental design was completely randomized with four replications. To monitor the process of decomposition, RB 956 911 sugarcane straw was air dried, and added in amounts equivalent to 4, 8 and 12 t ha-1 in wooden boxes. These wooden boxes were then collected monthly over a period of one year. The collected materials, was analyzed for the remaining amounts of dry matter (DM) and its C and N concentrations. The straw collected in Santa Maria were also analyzed for hemicellulose (HEM), cellulose (CEL) and lignin (LIG ) the values of DM and remaining C was adjusted in non-linear regression model. The results of this study demonstrated that the amount of sugarcane straw deposited on the surface does not affect the decomposition and release of carbon and nitrogen, and also the breakdown of bio-chemicals (cellulose, hemicellulose and lignin) in the straw. However, it was demonstrated that the site influenced the decomposition and carbon and nitrogen release from the straw, with the main factor controlling decomposition process was precipitation.